Effects of stature, age and vehicle motion on ingress movement. (24th August 2009) - Hanson, L.; Jeppson, M.; Rafstedt, P.; Yong, L.; , T. Falkmer
Vehicle ingress is an important automotive industry issue. End-users and production line assemblers perform similar ingress tasks. In this study, comparisons were made of the car ingress motion in 40 subjects of different statures, acting both as assemblers and end-users. Half of the subjects were under 28 years of age and the remaining were over 60. Results show no significant differences in motion patterns between assemblers and end-users, i.e., slow forward motion of the car on the assembly line had no effect on ingress patterns. This suggests that ergonomic departments working either with end-users or assemblers may instead cooperate or even be fully integrated. Stature significantly affected joint angle distribution and joint angle velocity distribution. No stature effect was found on time to perform ingress movements or on ingress technique. Age significantly affected all test parameters and is thus an issue for developers to consider along with anthropometric variables like stature. To facilitate age analysis, manikins in digital human modelling tools should be able to replicate the physical characteristics of different age groups and the movement behaviour of older people.